CDC42—A promising immune-related target in glioma - Jiang, Tao; Wang, Xianwei; Huang, Jiaming; Chen, Dong (Frontiers in Neuroscience, 2023)
Glioma is the worst prognostic neoplasm in the central nervous system. A polarity-regulating GTPase in cells, known as cell division cycle 42 (CdC42), has been proven to have its overactivation tightly connected to high tumor malignancy. The RNA-seq and protein expression of CDC42 in tumor and comparison tissues were analyzed based on the online tools; CDC42 was remarkably boosted in tumor tissues compared to normal controls. A total of 600 patients in the analysis set from The Cancer Genome Atlas (TCGA) database and 657 patients in the validation set from the Chinese Glioma Genome Atlas (CGGA) database were adopted. The expression of CDC42 in clinical features and biological functions of glioma was analyzed, including differential expression analysis, survival analysis, Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, and immune infiltration analysis. The enrichment of CDC42 was shown to be strongly associated with poor prognosis and terrible clinical indexes of glioma, including higher World Health Organization scale grade, wild-type isocitrate dehydrogenase 1 expression, O6-methylguanine-DNA methyltransferase non-methylated status, and 1p19q non-codeletion status (p < 0.0001). Functional enrichment analysis showed that CDC42 was highly correlated with immune and inflammatory responses in glioma. Additionally, the concentration extent of CDC42 was closely related to immune infiltration, immune checkpoints, and regulatory T (Treg) cell markers (CD4, CD25, and CD127). All evidence suggested that CDC42 may be a potential target for glioma immunotherapy.